(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: High-intensity frequency ultrasound (HIFU), a noninvasive ultrasound beam is focused on an exact tissue area that requires treatment. The highly focused energy from ultrasound causes the temperature of the tissue to rise, and the heat ablates the targeted tissue area. This therapy is gaining popularity and momentum globally for treating of brain, breast, prostate, thyroid, liver, kidney, bone tumors, fibroids, adenomyosis, and endometriosis. Additionally, it is used in placenta accreta syndrome and cesarean scar pregnancy. Cosmetics include rejuvenation of connective tissue on the face and vulva. Exploration of uses for the treatment of postpartum hemorrhage and cervical cancer is underway. Methods: An orientation meeting was held among Kenyatta National Hospital and the University of Nairobi multidisciplinary clinical and administrative personnel. This was followed by a study tour to China that engaged academia, researchers, clinicians, and radiologists to gain a first-hand understanding of the invention process, setup for procedures, and innovative applications of HIFU in both private and public health institutions. Results: Promising success data are generated in high-income counties. Recently introduced in West Africa with the possibility of introduction in Eastern Africa. Conclusion: Noninvasive targeted therapies are the new vogue, and there seems to be a globus application for HIFU. Acquisition of this technology, addressing the normative environment, competencies of multidisciplinary HCP, and research are needed in low- and middle-income countries. This novel technology can be cost-effective for the health system and improve patients’ experience. Furthermore, a combination of machine learning and clinical radiological imaging can be used as a predictor of tumor regrowth potential.